PENYULUHAN PENTINGNYA PEMBERIAN ASI EKSKLUSIF BAGI IBU DAN BAYI DI WILAYAH KERJA PUSKESMAS KAMPUNG JABI - Septi Maisyaroh Ulina Panggabean; Indah Dwi Puspita; Nur Afni (Awal Bros Journal of Community Development, 2022)
Exclusive breastfeeding is breastfeeding for the first 6 months of a baby's life without food or drink other than vitamins, drugs and ORS. The rate of exclusive breastfeeding in the Riau Islands based on the Indonesian Health Profile in 2019 was 81%, while in 2020 it was 58%. This shows that there is a decrease in exclusive breastfeeding for infants in the Riau Islands. This activity aims to increase the knowledge of pregnant women about the importance of exclusive breastfeeding for mothers and babies. This community service activity is carried out using the method of health education to the community in the form of counseling with the material presented, namely the Importance of Exclusive Breastfeeding for Mothers and Babies. The implementation of this counseling is done by using leaflets as a tool. The results of community service showed that there was an increase in knowledge of pregnant women after being given counseling, from 25% to 100%. There is an increase in knowledge of pregnant women after being given counseling, this shows that counseling has an influence on increasing one's knowledge.